The expression of the elements of the internal control system graphical representation - Giriūnas, Lukas; Mackevičius, Jonas (Buhalterinės apskaitos teorija ir praktika, 2014)
The results of the analysis of scientific literature showed that scientists disagree and do not share the same opinion on the expression of the elements of the internal control system. That is the situation that determines the transformation of internal control system models, its speed and variety. Thus, the analysis of the expression of graphical annotations of the internal control systems, provided in the scientific literature, allows to state that the internal control system can be depicted as a table with four legs, where each of them represents an element of the internal control system, whose existence is equivalent to the functioning of the internal control system. Another often found graphical annotation of the internal control system is the representation of its five elements in the form of an umbrella, which aims to demonstrate the precedence of the control environment over the other elements, i.e. the control environment encloses and protects the other four elements: risk assessment, control procedures, information and its transmission, and control monitoring. Meanwhile, the most common way to present the internal control system in the scientific literature is showing it in the form of a triangular pyramid, which clearly shows that the internal control system is based on the environment of the control. Therefore, to summarize all the internal control system models, provided in the scientific literature, it can be said that the company's system of internal control is designed to manage the risks, associated with the business environment; it is constantly changing and as a result must be continuously monitored and improved. It should be noted, that the analysis of the internal control models allow to state that the offered models are still not only very different from each other, but also do not specify any particular sequence of internal control effectiveness’ assessment; they only identify certain guidelines for the assessment, as a result, a new principal structurogram of the internal control effectiveness’ assessment model has been created. It should be stressed that the latter newly includes the coordination element, which was lacking in the identified models, presented in the scientific literature. It should be emphasized that the coordination of all the factors of employees is required in order to properly use the available resources and to save them, to guarantee high quality of products and services, to reduce all kinds of expenses, to obtain the best possible financial results.
Keywords: internal control system; control elements; graphical representation